The Concept of Independence of Central Bank on the Example of the National Bank of Poland - Agata Tarnacka (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2019)
The need for independence of the central bank results from the fiduciary nature of modern money. Independence of the central bank is generally understood as depriving the executive of the influence on the bank's decisions, while depriving the legislative authority of the right to interfere in the pursued monetary policy. Most talked about financial, functional and institutional independence. The results of the independence studies of the National Bank of Poland quoted in the article show that the level of NBP independence is high, often close to or equal to the maximum values for given measures. However, it should be noted that these studies relate to the formal (legal) independence of the NBP, and not the real one, because independence guaranteed by legal provisions does not necessarily correspond to the actual independence of the central bank. The legal regulations shape only the conditions of monetary authorities' actions, while the final result of these actions depends on the persons taking them. The article also presents arguments for both the central bank's independence and a summary.